(untitled) (Research, Society and Development, 2023)
Newborn care practices vary depending on cultural traditions within communities. These practices are essentially promoted by the figure of the grandmother, who takes an active part in care. This article aimed to analyze the influence of grandmothers on newborn care, according to the testimonies of postpartum women. And it corresponds to a descriptive study, exploratory, comparative and cross-sectional study, with qualitative methodology, carried out in Angola, with a non-probabilistic convenience sample, consisting of 40 Angolan mothers of newborns. There was a high presence and influence of grandmothers in care, marked by the transmission of knowledge rooted in their culture and beliefs, adopting care behaviors that are sometimes not recommended, as is the case of applying homemade solutions to the umbilical stump, which cause infections. Despite the ineffectiveness of these practices and the damage to the newborn’s health being scientifically proven, in many cases they continue to be the first choice in umbilical stump care. The results reveal the importance of implementing measures by the Ministry of Health of Angola, in order to reinforce and guide the intervention of health professionals, allowing the approach and inclusion of grandmothers in the promotion of health education, through culturally competent care, as recommended by the WHO, improving the quality of neonatal health in Angola.